2006
DOI: 10.2754/avb200675010115
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Toxic Effects and Induction of gGutathione S-transferase by Short-Chain Chlorinated Paraffins (SCCPs) and C-12 alkane (dodecane) in Xenopus laevis Frog Embryos

Abstract: Short chain chlorinated paraffins (SCCPs) are important industrial chemicals with high persistence in the environment but poorly characterized ecotoxicological effects. We studied embryotoxic effects of commercial mixture of SCCP (carbon length C-12, 56% of chlorine; CP56-12) and non-chlorinated n-alkane (dodecane, C-12) in the 96h Frog Embryo Teratogenesis Assay -Xenopus (FETAX). Only weak lethal effects were observed for both substances (the highest tested concentration 500 mg/L of both chemicals caused up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…SCCPs were listed in the Stockholm Convention on POPs in 2017, while the global production of MCCPs and LCCPs has increased recently (Castro et al, 2018). Available data indicate that while SCCPs do not demonstrate acute toxicity to aquatic organisms (Ali and Legler, 2010;Ren et al, 2018), they have shown chronic toxicity to frogs and rats, including developmental toxicity and neurotoxicity (Buryskova et al, 2006;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…SCCPs were listed in the Stockholm Convention on POPs in 2017, while the global production of MCCPs and LCCPs has increased recently (Castro et al, 2018). Available data indicate that while SCCPs do not demonstrate acute toxicity to aquatic organisms (Ali and Legler, 2010;Ren et al, 2018), they have shown chronic toxicity to frogs and rats, including developmental toxicity and neurotoxicity (Buryskova et al, 2006;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to the length of carbon chain, chlorinated paraffins are classified into short chain CPs (SCCPs, C 10–13 ), medium chain CPs (MCCPs, C 14–17 ) and long chain CPs (LCCPs, C 18–30 ) with chlorine mass contents from 30 to 70% (Pellizzato et al, 2007). Among CPs, SCCPs have been under review for inclusion in Stockholm Convention on Persistent Organic Pollutants (POPs) (UNEP, 2015) because of their long-distance atmospheric transport (Tomy et al, 2000), persistence (Iozza et al, 2008), bioaccumulation (Houde et al, 2008) and toxicities in the environment (Burýšková et al, 2006; Cooley et al, 2001; Geng et al, 2015; Madeley and Birtley, 1980). The toxicities of SCCPs are generally more prominent than those of MCCPs and LCCPs (Feo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is considered not toxic by the International Fragrance Association (IFRA) Environmental Standards (Api et al, 2020) and no limits have been set for its use by the EU regulation on fertilizing products (EU 2019/1009) (Regulation EU, 2019). Even though dodecane is considered a safe substance, literature studies have shown that it can cause cell death, skin irritation in rats, developmental impairment in aquatic organisms and papillomas in mice (Baxter and Miller, 1987;Babu et al, 2004;Burýšková et al, 2006;Kleinegris et al, 2011). These evidences highlight the need to collect further data on the exposure assessment of dodecane.…”
Section: Acenaphthylenementioning
confidence: 99%